Contribution of copy number variants to schizophrenia from a genome-wide study of 41,321 subjects - Marshall, Christian R.; Rietschel, Marcella (Nature genetics, 2017)
Copy number variants (CNVs) have been strongly implicated in the genetic etiology of schizophrenia (SCZ). However, genome-wide investigation of the contribution of CNV to risk has been hampered by limited sample sizes. We sought to address this obstacle by applying a centralized analysis pipeline to a SCZ cohort of 21,094 cases and 20,227 controls. A global enrichment of CNV burden was observed in cases (odds ratio (OR) = 1.11, P = 5.7 × 10−15), which persisted after excluding loci implicated in previous studies (OR = 1.07, P = 1.7 × 10−6). CNV burden was enriched for genes associated with synaptic function (OR = 1.68, P = 2.8 × 10−11) and neurobehavioral phenotypes in mouse (OR = 1.18, P = 7.3 × 10−5). Genome-wide significant evidence was obtained for eight loci, including 1q21.1, 2p16.3 (NRXN1), 3q29, 7q11.2, 15q13.3, distal 16p11.2, proximal 16p11.2 and 22q11.2. Suggestive support was found for eight additional candidate susceptibility and protective loci, which consisted predominantly of CNVs mediated by nonallelic homologous recombination.
Published online: 21 November 2016
Gesehen am 03.04.2018